2017
DOI: 10.1108/ijph-07-2016-0031
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based recommendations to improve reproductive healthcare for incarcerated women

Abstract: Purpose The purpose of this paper is to describe standards for evidence-based reproductive healthcare for incarcerated women. Design/methodology/approach The literature on reproductive healthcare in the US criminal justice system and recommendations from professional organizations were reviewed and critical areas of concern were identified. Within these areas, studies and expert opinion were synthesized and policy recommendations were formulated through an iterative process of group discussion and document rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…22 Women's experiences of menopausal symptoms were observed to be particularly uncomfortable within detention spaces. 34,38,40 Menopausal sequelae are all typically exacerbated by prison conditions (and by a lack of health support). 33,41 Common symptoms requiring both medical and general health-related supports in prisons included insomnia, hot flushes, night sweats, vaginal bleeding, urinary incontinence, lower bone density, fatigue, and mood changes.…”
Section: Discussion and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Women's experiences of menopausal symptoms were observed to be particularly uncomfortable within detention spaces. 34,38,40 Menopausal sequelae are all typically exacerbated by prison conditions (and by a lack of health support). 33,41 Common symptoms requiring both medical and general health-related supports in prisons included insomnia, hot flushes, night sweats, vaginal bleeding, urinary incontinence, lower bone density, fatigue, and mood changes.…”
Section: Discussion and Observationsmentioning
confidence: 99%
“…Complexities of menopause and comorbid health of women living in detention settings are ill considered (psychiatric illness, drug dependence, prior trauma) 37 . Global reviews/opinion pieces observed the lack of life-course appropriate information, mental health supports, and pharmacological and lifestyle interventions for detained menopausal women, and underscored the need for effective personalized management of menopause in prison 33,38 . Critical prison failures center on the lack of medicines, and denial of and lack of access to free age- and gender-specific care equivalent to that in the community and to lifestyle interventions, causing considerable distress (contra Bangkok Rules 6, 8, 10, 16).…”
Section: Discussion and Observationsmentioning
confidence: 99%
“…Se recomienda que se ofrezca a todas las mujeres encarceladas programas integrales de tratamiento y prevención de ITS, y las mujeres encarceladas se hacen eco de esta necesidad. Se ha demostrado que los programas que enfatizan la educación sobre ITS, combinada con la capacitación de habilidades, la vivienda y el empleo disminuyen el comportamiento de riesgo para estas infecciones (30).…”
Section: Discussionunclassified
“…Additionally, there were no incarcerated women included in this study. Incarcerated women have their own unique challenges such as, consistent access to a full spectrum of women's healthcare, higher rates of PTSD than men, and complexities in reporting sexual misconduct by prison staff [8,93,94]. Women are more likely to have lived with minor children up to the point of arrest than men, and more incarcerated women report being mothers than incarcerated men report being fathers [95].…”
Section: Future Direc Tionsmentioning
confidence: 99%